Analysis of Factors Affecting Regional Original Income in West Lombok Regency in 2010-2022: Analisis Faktor yang Mempengaruhi Pendapatan Asli Daerah di Kabupaten Lombok Barat Tahun 2010-2022 - Lidia Ifana Dwi Kusuma; Wahyunadi; Sujadi (Economy and Finance Enthusiastic, 2023)
National development is a process of change that takes place in a planned and sustainable manner with the aim of increasing the standard of living of the people of a nation. This research aimed to analyze the effect of government spending, GRDP on local revenue in West Lombok Regency in 2010-2020. The data used is secondary data to find out whether there is an influence on Regional Original Income in West Lombok Regency in 2010-2021. The collected data were analyzed using data analysis which first tested the classical assumptions before testing the hypothesis, testing the hypothesis in this study using multiple regression analysis with the t test, f test and test the coefficient of determination. The results showed that the coefficient of determination obtained a value of 0.329 which means that 32.9% of local revenue is influenced by government spending and gross regional domestic product. The results of the hypothesis test show that government spending has no positive and significant effect on local own income, gross regional domestic product has a positive and significant effect on regional original income.